Use of ISSR Markers for Molecular Genetic Analysis of Eucalyptus tereticornis - Kumar, Adarsh; Kumari, Sarika (Research in Biotechnology, 2014)
Genetic variation between 10 trees of Eucalyptus tereticornis was evaluated using inter simple sequence repeats (ISSR) markers. PIC (polymorphism information content), EMR, MI value and Rp value was obtained for per primer combination. These values for ISSR suggested that the marker system were effective in determining polymorphisms. The similarity coefficient and the UPGMA clustering method were employed to construct the dendrogram. ISSR marker system was found to be useful for the genetic diversity studies in E. tereticornis.